Kesenjangan Formulasi dan Implementasi Strategi Serta Dampaknya terhadap Kinerja Rumah Sakit - Nden Zulvia Afifah; I Gede Sutawan; Purwadhi Purwadhi; Yani Restiani Widjaja (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
Hospital performance is highly influenced by the alignment between strategy formulation and implementation, yet gaps often occur, affecting operational efficiency, service quality, and patient satisfaction. This study aims to analyze the strategy gap and its impact on hospital performance, as well as to identify factors influencing the success of strategy execution, including human resources, resource allocation, and information technology support. A Systematic Literature Review (SLR) approach was employed, analyzing 35 articles published between 2015 and 2025 from Scopus, PubMed, Google Scholar, and Sinta databases. The results indicate that strategy gaps are caused by limited communication, uneven resource allocation, varying staff capacities, and insufficient monitoring and technological support. Hospitals that successfully align strategy formulation and implementation through staff involvement, effective leadership, integrated management information systems, and well-structured career paths and incentives demonstrate significant improvements in operational efficiency, service quality, and patient satisfaction. The study concludes that strategy alignment is a key factor in enhancing hospital performance and recommends developing integrated strategies, strengthening human resource development programs, utilizing technology, and implementing continuous monitoring to minimize gaps and ensure high-quality healthcare services.